Fiscal Decentralization and Economic Growth: The Mediating Role of Gross Fixed Capital Formation in Java 2014–2024 - Anastasya Putri Santoso; Grace Natalia Marpaung (Danadyaksa: Post Modern Economy Journal, 2026)
This study examines the effect of fiscal decentralization, proxied by Regional Own-Source Revenue, Capital Expenditure, and Intergovernmental Transfers, on economic growth, and evaluates the mediating role of Gross Fixed Capital Formation in this relationship across six provinces on Java Island during the period 2014–2024. The study applies a quantitative approach using annual panel data obtained from Regional Government Financial Reports and the Central Statistics Agency. The analysis employs path analysis and the Sobel test under the Common Effect Model. The results show that Regional Own-Source Revenue and Capital Expenditure exert a positive and significant effect on both economic growth and Gross Fixed Capital Formation, whereas Intergovernmental Transfers exhibit a positive but insignificant effect on both variables. Gross Fixed Capital Formation significantly mediates the effect of Regional Own-Source Revenue and Capital Expenditure on economic growth, but does not mediate the effect of Intergovernmental Transfers. These results indicate that the transmission of fiscal decentralization to economic growth through capital accumulation operates effectively only through fiscally independent and productive components.